Deleterious impact of mismatching for human leukocyte antigen-C in presensitized recipients of kidney transplants - Tran, Thuong Hien; Döhler, Bernd; Heinold, Andreas; Scherer, Sabine; Ruhenstroth, Andrea; Opelz, Gerhard (Transplantation, 2011)
BACKGROUND: Allocation of deceased donor kidneys is commonly based on matching for human leukocyte antigen (HLA)-A, -B, and -DR, whereas HLA-C is currently disregarded. We investigated the influence of HLA-C compatibility on renal allograft survival. In addition, we tested an approach of matching for HLA-C epitopes. METHODS: A cohort of 2260 deceased donor kidney transplants were typed for HLA-C using polymerase chain reaction-sequence specific primer method. Samples for DNA typing, serum results on presensitization (lymphocytotoxicity), and clinical data were provided by transplant centers participating in the Collaborative Transplant Study. RESULTS: HLA-C mismatch was found to be associated with significantly decreased graft survival in presensitized (P<0.001) but not in non-presensitized (P=0.75) recipients. Mismatch of certain HLA-C epitopes seemed to be more influential than others, with mismatches showing a negative impact on graft survival in presensitized patients. CONCLUSIONS: HLA-C mismatch has a substantial deleterious effect on graft survival in presensitized kidney recipients. Our study points out the need for investigations directed at identifying donor-specific HLA-C antibodies and evaluating their relevance in transplantation. In view of the fact that current assays for determining HLA-C specific antibodies are hampered by additional detection of clinically irrelevant antibodies, matching for HLA-C may provide a reasonable approach to improve transplant outcomes in presensitized kidney transplant recipients.